Hypothermia Prevents Retinal Damage Generated by Optic Nerve Trauma in the Rat - Rey Funes, Manuel (2017)
Ocular and periocular traumatisms may result in loss of vision. Hypothermia provides a beneficial intervention for brain and heart conditions and, here, we study whether hypothermia can prevent retinal damage caused by traumatic neuropathy. Intraorbital optic nerve crush (IONC) or sham manipulation was applied to male rats. Some animals were subjected to hypothermia (8 °C) for 3 h following surgery. Thirty days later, animals were subjected to electroretinography and behavioral tests. IONC treatment resulted in amplitude reduction of the b-wave and oscillatory potentials of the electroretinogram, whereas the hypothermic treatment significantly (p < 0.05) reversed this process. Using a descending method of limits in a two-choice visual task apparatus, we demonstrated that hypothermia significantly (p < 0.001) preserved visual acuity. Furthermore, IONC-treated rats had a lower (p < 0.0001) number of retinal ganglion cells and a higher (p < 0.0001) number of TUNEL-positive cells than sham-operated controls. These numbers were significantly (p < 0.0001) corrected by hypothermic treatment. There was a significant (p < 0.001) increase of RNA-binding motif protein 3 (RBM3) and of BCL2 (p < 0.01) mRNA expression in the eyes exposed to hypothermia. In conclusion, hypothermia constitutes an efficacious treatment for traumatic vision-impairing conditions, and the cold-shock protein pathway may be involved in mediating the beneficial effects shown in the retina.